Phthalimide Analogs Enhance Genotoxicity of Cyclophosphamide and Inhibit Its Associated Hypoxia - Gamal-Eldeen, Amira M.; Agwa, Hussein S.; Zahran, Magdy A.-H.; Raafat, Bassem M.; El-Daly, Sherien M.; Banjer, Hamsa J.; Almehmadi, Mazen M.; Alharthi, Afaf; Hawsawi, Nahed M.; Althobaiti, Fayez; Abo-Zeid, Mona A. M. (Frontiers in Chemistry, 2022)
Cyclophosphamide (CP) is a mutagen that is used as a cancer chemotherapy, due to its genotoxicity ‎and as immunosuppressive agent. Thalidomide (TH) is another cancer chemotherapeutic drug. In ‎this study, the cytogenotoxicity and hypoxia modulatory activity of two phthalimide analogs of TH ‎have been evaluated with/without CP. Both analogs have increased CP-stimulated chromosomal ‎aberrations than that induced by TH, including gaps, breaks/fragments, deletions, multiple ‎aberrations and tetraploidy. The analogs have elevated the cytotoxic effect of CP by inhibiting the ‎mitotic activity, where analog 2 showed higher mitosis inhibition. CP has induced binucleated and ‎polynucleated bone marrow cells (BMCs) while micronuclei (MN) are absent. TH and analogs have ‎elevated the CP-stimulated binucleated BMCs, while only analogs have increased the CP-induced ‎polynucleated BMCs and inhibited the mononucleated BMCs. MN-BMCs were showed together with ‎mononucleated, binucleated and polynucleated cells in CP group. Both analogs have elevated ‎mononucleated and polynucleated MN-BMCs, whereas in CP presence, TH and analogs have ‎enhanced mononucleated and binucleated MN-BMCs. The analogs significantly induce DNA ‎fragmentation in comet assay, where analog 1 is the strongest inducer. The treatment of mice with ‎CP has resulted in a high hypoxia status as indicated by high pimonidazole adducts and high HIF-1α ‎and HIF-2α concentrations in lymphocytes. Analogs/CP-treated mice showed low pimonidazole ‎adducts. Both analogs have inhibited HIF-1α concentration but not HIF-2α. Taken together, the study ‎findings suggest that both analogs have a higher potential to induce CP-genotoxicity than TH and ‎that both analogs inhibit CP-hypoxia via HIF-1α-dependent mechanism, where analog 1 is more ‎potent anti-hypoxic agent than analog 2. Analog 1 is suggested as adjacent CP-complementary ‎agent to induce CP-genotoxicity and to inhibit CP-associated hypoxia.‎